2018
DOI: 10.1088/1742-6596/1028/1/012164
|View full text |Cite
|
Sign up to set email alerts
|

The Profile of Students’ Mathematical Problem Solving on the Topic of Two-Variable Linear Equation Systems Based on Thinking Styles

Abstract: Abstract. The study aimed to describe the profile of problem of solving grade VIII students at MTs Al-Murahmah, based on thinking styles. The results of the research show the profile of mathematics problem solving of; 1) concrete sequential student are: a) understanding mathematics problems, that tended to organize facts, b) conducting problem solving, that tended to work algorithmically in each stage problem solving; 2) abstract sequential students are: a) understanding the problems, which had tendency to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…Two thinking styles found in the present study, Random Abstract and Sequential Concrete, have a distinct process of thinking in establishing a definition, making the opininion, and drawing the conclusion. Similar cases were also found by Djadir et al (2018) where students with Sequential Concrete tend to organize facts, obtain systematically, and present information in a whole range of things, while Random Abstract students tend to have trial and error in solving problems. However, these differences do not preclude success in constructing mathematics knowledge.…”
Section: Drawing Conclusion Drawing Conclusion Analogicallysupporting
confidence: 66%
See 2 more Smart Citations
“…Two thinking styles found in the present study, Random Abstract and Sequential Concrete, have a distinct process of thinking in establishing a definition, making the opininion, and drawing the conclusion. Similar cases were also found by Djadir et al (2018) where students with Sequential Concrete tend to organize facts, obtain systematically, and present information in a whole range of things, while Random Abstract students tend to have trial and error in solving problems. However, these differences do not preclude success in constructing mathematics knowledge.…”
Section: Drawing Conclusion Drawing Conclusion Analogicallysupporting
confidence: 66%
“…There are also several studies (e.g. Myers & Dyer, 2006;Zakir, 2015;Setyawan, 2017;Sahatcija, Ora, & Ferhataj, 2017;Djadir, Upu, & Sulfianti, 2018) which specifically refer to Gregorc's (1982) model of thinking. Myers and Dyer (2006) found that students with deeply embedded Sequential Abstract learning style preferences exhibited significantly higher critical thinking.…”
Section: A Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the work of Djadir, Hamzah Upu, four research subjects were correlated with different styles of thinking: sequential concrete, sequential abstract, random concrete, and random abstract. It was found that mathematical problem solving profiles influence students' choice of different strategies, as well as the quality and productivity of problem solving [13].…”
Section: Introductionmentioning
confidence: 99%
“…He has a significant role in various disciplines and advances the power of human thought. To master technology and create a future, one needs mastery in mathematics at the beginning of school [1]. This is one of the factors underlying mathematics taught at all levels of education.…”
Section: Introductionmentioning
confidence: 99%